2014
DOI: 10.1111/ijpo.251
|View full text |Cite
|
Sign up to set email alerts
|

Apelin and G212A apelin receptor gene polymorphism in obese and diabese youth

Abstract: Obese (especially diabese) youngsters demonstrated lower serum apelin levels; the G212A polymorphism of the APLNR gene was found to exert a favourable effect on circulating apelin levels in childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 30 publications
(61 reference statements)
5
23
3
1
Order By: Relevance
“…APLNR encodes a family member of the G protein-coupled receptors. Several studies have investigated polymorphisms of APLNR and the susceptibility of DCM (37)(38)(39). In addition, the 212A allele of the APLNR G212A polymorphism is considered to be significantly associated with reduced risk of idiopathic DCM (39), suggesting that alteration of this gene may influence the DCM.…”
Section: Itga11 Col6a1 Lamc2mentioning
confidence: 99%
See 1 more Smart Citation
“…APLNR encodes a family member of the G protein-coupled receptors. Several studies have investigated polymorphisms of APLNR and the susceptibility of DCM (37)(38)(39). In addition, the 212A allele of the APLNR G212A polymorphism is considered to be significantly associated with reduced risk of idiopathic DCM (39), suggesting that alteration of this gene may influence the DCM.…”
Section: Itga11 Col6a1 Lamc2mentioning
confidence: 99%
“…Several studies have investigated polymorphisms of APLNR and the susceptibility of DCM (37)(38)(39). In addition, the 212A allele of the APLNR G212A polymorphism is considered to be significantly associated with reduced risk of idiopathic DCM (39), suggesting that alteration of this gene may influence the DCM. In the present study, PENK and APLNR were identified as two crucial genes in module 2, suggesting that they may exert more important functions in DCM than other genes.…”
Section: Itga11 Col6a1 Lamc2mentioning
confidence: 99%
“…Interestingly, obese subjects with impaired glucose metabolism only had lower apelin levels than controls. In the obese subgroup, carriers of the major G-allele had lower apelin levels [174]. However, the investigated sample size and so the statistical power was low (90 obese vs. 90 controls).…”
Section: Complement Component 3a Receptor 1 (C3ar1) Apelin Receptor mentioning
confidence: 91%
“…However, the relationship between the receptor SNP and serum apelin levels was not investigated [173]. To date, the rs11544374 G/A APJ polymorphism only was found to exert an effect on circulating apelin levels in childhood obesity ( Table 2) [174]. Interestingly, obese subjects with impaired glucose metabolism only had lower apelin levels than controls.…”
Section: Complement Component 3a Receptor 1 (C3ar1) Apelin Receptor mentioning
confidence: 99%